Studies on storage stability of probiotic shrikhand obtained from safflower (Carthamus tinctorius)-blended milk - Jadhav, V P; Hiremath, Jayashri P; Kalyankar, S D; Khedkar, C D (Indian Journal of Dairy Science, 2019)
Shrikhand is a semi solid, sweetish-sour, whole milk product, prepared from lactic fermented curd. The curd (dahi) is partially strained through a muslin cloth to remove the whey to yield Chakka. Sugar, flavour, colour and dry fruits/condiments are mixed into Chakka to form a soft homogenous mass known as Shrikhand. It is a nutritionally dense fermented milk product. Its nutritional and therapeutic value can further be enhanced by incorporating filled milk, fruit pulp or probiotics. Safflower seed is rich in essential fatty acid (78% linoleic acid). Safflower milk blended probiotic Shrikhand was developed by using safflower milk, lactic culture, probiotic culture, sugar, powdered safflower petals (colorant) and mango flavour. Among the various levels of safflower milk-cow milk (CM) blends, lactic cultures and probiotic cultures tried in preparation of probiotic dahi, the blends of 30:70 safflower milk-CM, scored the highest. Chakka prepared from optimized probiotic Dahi used for Shrikhand preparation using 40% sugar, 0.1% colour and 500 ppm mango flavour was adjudged the best. Modified Shrikhand showed 12.47, 9.40, 40.70, 63.77 and 1.09% of fat, protein, carbohydrate, total solids and titratable acidity (% LA), respectively. Storage studies at refrigeration temperature (5±1°C) revealed that the product retained acceptability for a period of 21 days.